Clinical, epidemiological, and spatial features of human rabies cases in Metro Manila, the Philippines from 2006 to 2015. - Ferdinand D Guzman; Yuta Iwamoto; Nobuo Saito; Eumelia P Salva; Efren M Dimaano; Akira Nishizono; Motoi Suzuki; Oladeji Oloko; Koya Ariyoshi; Chris Smith; Christopher M Parry; Rontgene M Solante (Public Library of Science (PLoS), 2022)
Rabies remains a public health problem in the Philippines despite the widespread provision of rabies vaccines and rabies immunoglobulin (RIG) as post-exposure prophylaxis (PEP). Detailed descriptions of recent human rabies cases in the Philippines are scarce. This study aimed to describe the clinical, epidemiological, and spatial features of human rabies cases between January 1, 2006, and December 31, 2015. We conducted a retrospective hospital-based case record review of all patients admitted to one referral hospital in Manila who received a clinical diagnosis of rabies. During the 10-year study period there were 575 patients (average 57.5 cases per year, range 57 to 119) with a final diagnosis of rabies. Most patients were male (n = 404, 70.3%) and aged ≥ 20 years (n = 433, 75.3%). Patients mostly came from the National Capital Region (n = 160, 28.0%) and the adjacent Regions III (n = 197, 34.4%) and IV-A (n = 168, 29.4%). Case mapping and heatmaps showed that human rabies cases were continuously observed in similar areas throughout the study period. Most patients had hydrophobia (n = 444, 95.5%) and/or aerophobia (n = 432, 93.3%). The leading causative animals were dogs (n = 421, 96.3%) and cats (n = 16, 3.7%). Among 437 patients with animal exposure history, only 42 (9.6%) had been administered at least one rabies vaccine. Two patients (0.5%), young children bitten on their face, had received and a full course of rabies vaccine. Human rabies patients were continuously admitted to the hospital, with no notable decline over the study period. The geographical area in which human rabies cases commonly occurred also did not change. Few patients received PEP and there were two suspected cases of PEP failure. The retrospective design of this study was a limitation; thus, prospective studies are required.